Maya (image) in indigenous Riau world-view: A forgotten concept of Malayan animist thought and ritual practice - Nathan Porath (2018)
© Malaysian Branch of the Royal Asiatic Society. The early literature on Malay animism and magic includes a passing reference to a concept called maya. This reference is hardly noticeable in the literature, and when Kirk Endicott wrote his Malay Magic, he omitted the word altogether. In this article the author uses ethnographic material from the Malayanspeaking Orang Sakai of Riau to examine the concept of maya (image) as it relates to a 'lifeless soul' inherent in material objects, giving physical objects vitality of form, appearance and use.